Theoretical and experimental determination of tool life in hot machining of austenitic manganese steel - Özler, L; Inan, A; Özel, C (Elsevier Sci Ltd, 2001)
In this study, an expression for the tool life of a sintered carbide tool machining heated austenitic manganese steel was developed. The influence of surface temperature, cutting speed, feed rate, and depth of cut on the tool life were investigated. Afterwards, an expression for the effects of cutting conditions on tool life were determined using a mathematical model developed by a factorial regression method. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: hot machining; tool life; austenitic manganese steel